Emotional Intelligence and Burn out among nurses working in tertiary hospitals of KPK: Emotional Intelligence and Burn out - Ullah , Shakir; Rafique , Safia; Sultan, Amir; Ahmed , Fayaz; Rehman , Aziz-ur-; Khan, Atif (Pakistan Journal of Health Sciences, 2022)
Emotional Intelligence (EI) is the capability of people to recognize the emotions of themselves and others; it consists of self-awareness, self-management, social awareness, and relationship management. Healthcare professionals with exceptional emotional intelligence are able to identify emotions in others and modify their own emotions to fit the situation. Objective: The purpose of the study was to investigate the EI and burnout among nurses employed in tertiary care hospitals in KPK. Methods: The study design was cross-sectional descriptive, conducted in 2 tertiary care hospitals from March 2022 to July 2022, with a sample size of 104. Data were collected through 2 valid and reliable questionnaires; the Schutte Self-report EI Test and the Maslach Burnout Inventory. Results: The male participants of the study were 51.9% and the females were 48.1%, the large numbers of staff response were positive towards emotional intelligence 78% and the negative emotional intelligence was 22%. The mean and standard deviation scores of (MOTE 29.09 ± 9.01, MOE 33.19 ± 9.78, POE 31.94 ± 9.61, and UOE 22.9 ± 5.99) were more than the cut-off values. The high burnout was 36%, the low burnout was 33%, and the average burnout was 31%. Conclusions: Nurses working in tertiary care hospitals have positive emotional intelligence, but burnout in the majority of participants was high due to a shortage of staff and an increasing number of patients.